How Per- and Poly-Fluoroalkyl Substances Affect Gamete Viability and Fertilization Capability: Insights from the Literature - Cielle Lockington; Laura A. Favetta (MDPI AG, 2024)
There has been emerging research linking per- and poly-fluoroalkyl substances (PFAS) to gamete viability and fertility. PFAS, prevalent in the environment and water supplies, undergo slow degradation due to their C-F bond and a long half-life (2.3-8.5 years). In females, PFAS inhibit the hypothalamic-pituitary-gonadal (HPG) axis, reducing follicle-stimulating hormone (FSH) and luteinizing hormone (LH) levels, leading to the inhibition of androgen and estradiol production. PFAS have been found to cause detrimental effects on egg quality through impairing folliculogenesis. In males, PFAS can impair sperm motility and morphology: two fundamental qualities of successful fertilization. PFAS exposure has been proven to inhibit testosterone production, sperm capacitation, and acrosomal reaction. After fertilization, the results of PFAS exposure to embryos have also been investigated, showing reduced development to the blastocyst stage. The aim of this review is to report the main findings in the literature on the impact of PFAS exposure to gamete competency and fertilization capability by highlighting key studies on both male and female fertility. We report that there is significant evidence demonstrating the negative impacts on fertility after PFAS exposure. At high doses, these environmentally abundant and widespread compounds can significantly affect human fertility.